Accuracy of D-dimer as a Predictive Biomarker for Outcome in Head Injured Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Masdiyanto, Gayuh Prastya; Agung Muda Patih; Erial Bahar (Sriwijaya Journal of Surgery, 2023)
Introduction: D-dimer reflects the upregulation of the overall hemostatic system upon admission. If D-dimer levels increase, coagulation disorders appear. This is considered a poor prognostic factor. High D-dimer levels reflect the severity of brain injury. Activation of systemic coagulation causes extensive intravascular fibrin deposition and a decrease in platelets and coagulation factors. This study aimed to assess the accuracy of D-dimer as a predictive biomarker for outcomes in head injury patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study is a prospective prognostic test study to test the sensitivity and specificity of D-dimer for prediction mortality in patients with severe head injuries at Dr. Mohammad Hoesin General Hospital (RSMH) Palembang in the period June 2023 to August 2023. A total of 47 research subjects participated in this study. Results: Post 24-hour D-dimer levels have a cut-off point of 11.78 mg/L, which has high accuracy in poor outcomes. D-dimer levels after 5 days have a cut-off point value of 2.3 mg/L and have high sensitivity in predicting poor outcomes, and the value of the difference in changes in D-dimer based on poor outcome patients have a cut-off point of 3.33 mg/L, which has a high sensitivity in predicting a poor prognosis. Conclusion: D-dimer levels are quite accurate as a predictive biomarker for outcomes in head injury patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.